2009
DOI: 10.1017/s1366728909990289
|View full text |Cite
|
Sign up to set email alerts
|

The effects of contact on native language pronunciation in an L2 migrant setting

Abstract: The primary aim of this study was to determine whether native speakers of German living in either Canada or the Netherlands are perceived to have a foreign accent in their native German speech. German monolingual listeners (n = 19) assessed global foreign accent of 34 L1 German speakers in Anglophone Canada, 23 L1 German speakers in the Dutch Netherlands, and five German monolingual controls in Germany. The experimental subjects had moved to either Canada or the Netherlands at an average age of 27 years and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 17 publications
8
128
0
3
Order By: Relevance
“…The first more in-depth investigations of a range of measures of lexical diversity and fluency as well as overall accuracy, however, failed to find any consistent 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 relationship with a broad range of language exposure and use measures (Schmid, 2007;. The absence of an effect of exposure, and in particular of the frequency of use in infomal contexts, has since been replicated across a host of investigations of attrition across a range of linguistic levels, such as perceived foreign accent (Hopp & Schmid, 2013;de Leeuw, Schmid & Mennen, 2010) This suggests that a much more prominent role should be given in investigations of bilingual development to the notion of code-switching: Language systems are probably never co-activated more closely than in speakers who are dense code-switchers (Green …”
Section: Exposure and Co-activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first more in-depth investigations of a range of measures of lexical diversity and fluency as well as overall accuracy, however, failed to find any consistent 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 relationship with a broad range of language exposure and use measures (Schmid, 2007;. The absence of an effect of exposure, and in particular of the frequency of use in infomal contexts, has since been replicated across a host of investigations of attrition across a range of linguistic levels, such as perceived foreign accent (Hopp & Schmid, 2013;de Leeuw, Schmid & Mennen, 2010) This suggests that a much more prominent role should be given in investigations of bilingual development to the notion of code-switching: Language systems are probably never co-activated more closely than in speakers who are dense code-switchers (Green …”
Section: Exposure and Co-activationmentioning
confidence: 99%
“…On the other hand, bilingual speakers who frequently use one of their languages in a setting in which it is inappropriate to code-switch, for instance at work or with monolinguals, especially professionals such as (simultaneous) interpreters (Woumans, Ceuleers, van der Linden, Szmalec & Duyck, 2015), have extensive practice in minimizing co-activation and crosslinguistic interference, in addition to a more developed monitoring system. Several studies have found that it is mainly speakers who use the L1 regularly in professional contexts who show relatively minimal attrition effects, while there is no such benefit among speakers who use the L1 mainly within the family or with friends (de Leeuw, Schmid & Mennen, 2010;Schmid, 2007;.…”
Section: Exposure and Co-activationmentioning
confidence: 99%
“…A number of studies have shown that under these circumstances, cross-linguistic interactions may occur more commonly. De Leeuw, Schmid and Mennen (2010), for instance, found that native German speakers with long-term residence in an L2-speaking environment were more likely to be perceived as non-native in their L1 if they regularly engaged in code-switching.…”
Section: Cross-linguistic Interactions and Input Settingsmentioning
confidence: 99%
“…This requires dual language activation and further increases the likelihood of cross-linguistic interactions (de Leeuw et al, 2010). In sum, the context in which Sofia and Maya hear Italian explains why the language was affected by English, but not by Spanish.…”
Section: Cross-linguistic Interactionsmentioning
confidence: 99%
“…To date, the factor that has been shown to exert the greatest effect on L1 maintenance among speakers who arrived in the L2 setting as children or young adolescents is, not surprisingly, the degree of L1 contact (e.g. Bylund, Abrahamsson, and Hyltenstam 2010;de Leeuw, Schmid, and Mennen 2010;Hakuta and D'Andrea 1992;YeniKomshian, Flege, and Liu 2000). However, studies on L1 attrition in speakers who arrived in the L2 setting before adulthood seldom take into account the possibility that their participants could also have received formal instruction in the L1 through some form of heritage language (HL) education.…”
Section: Introductionmentioning
confidence: 99%